Effects of Post- Heat Treatment of Nanocrystalline ZnO Thin Films deposited on Zn-Deposited FTO Substrates - 김익현; 김영규; 남기웅; 임재영 (대한금속·재료학회지, 53(10), 2015)
The effects of heat-treatment temperature on the structural and optical properties of ZnO thin films were investigated with field-effect scanning electron microscopy (SEM), X-ray diffraction analysis, and photoluminescence (PL) measurements. The ZnO thin films were grown on Zn-deposited fluorine-doped tin oxide substrates by sol-gel spin coating. The SEM images of the samples showed that their surfaces had a mountain-chain-like structure. The film annealed at 400 ℃ had the highest degree of alignment along the c-axis, and its residual stress was close to zero. The PL spectra of the ZnO thin films consisted of sharp near-band-edge emissions (NBE) and broad deep-level emissions (DLE) in the visible range. The DLE peaks exhibited a green-to-red shift with an increase in the temperature. The highest INBE/IDLE ratio was observed in the film annealed at 400 ℃. Thus, the optimal temperature for growing high-quality ZnO thin films on Zn-deposited FTO substrates is 400 ℃ KCI Citation Count: 2